Varstrometry for Off-nucleus and Dual Sub-kiloparsec Active Galactic Nuclei (VODKA): Very Long Baseline Array Searches for Dual or Off-nucleus Quasars and Small-scale Jets - Chen, Yu-Ching; Liu, Xin; Lazio, Joseph; Breiding, Peter; Burke-Spolaor, Sarah; Hwang, Hsiang-Chih; Shen, Yue; Zakamska, Nadia L. (The Astrophysical journal, 2023)
Dual and off-nucleus active supermassive black holes are expected to be common in the hierarchical structure formation paradigm, but their identification at parsec scales remains a challenge due to strict angular resolution requirements. We conducted a systematic study using the Very Long Baseline Array (VLBA) to examine 23 radio-bright candidate dual and off-nucleus quasars. The targets are selected by a novel astrometric technique ( varstrometry ) from Gaia, aiming to identify dual or off-nucleus quasars at (sub)kiloparsec scales. Among these quasars, eight exhibit either multiple radio components or significant (>3 σ ) positional offsets between the VLBA and Gaia positions. The radio emission from the three candidates, which exhibit multiple radio components, is likely to originate from small-scale jets based on their morphology. Among the remaining five candidates with significant VLBA-Gaia offsets, three are identified as potential dual quasars at parsec scales, one is likely attributed to small-scale jets, and the origin of the last candidate remains unclear. We explore alternative explanations for the observed VLBA-Gaia offsets. We find no evidence for optical jets at kiloparsec scales, nor any contamination to Gaia astrometric noise from the host galaxy; misaligned coordinate systems are unlikely to account for our offsets. Our study highlights the promise of the varstrometry technique in discovering candidate dual or off-nucleus quasars and emphasizes the need for further confirmation and investigation to validate and understand these intriguing candidates.